Penerapan Prinsip Tanggung Jawab Keamanan dalam Penanggulangan Pencemaran Maritim Di Laut Nias Utara: Tinjauan Kepentingan Nasional Indonesia - Octavinus Cornelis Seba, Roberto (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
This study analyzes the application of the strict liability principle in addressing marine pollution caused by ships in the North Nias Waters, focusing on the MT AASHI asphalt spill incident and its implications for Indonesia’s national interests. Employing a normative legal research design with a qualitative approach, the study investigates legal responses, regulatory frameworks, and international obligations through document analysis and field-based data. The research highlights that the Indonesian government responded by forming a joint investigative team and demanding accountability from the foreign-flagged vessel, which operated under a flag of convenience without clear insurance protection. The study identifies Indonesia’s key national interests in this case: environmental security, economic sovereignty, and jurisdictional authority over its Exclusive Economic Zone. As a party to MARPOL and UNCLOS, Indonesia upholds international obligations to prevent marine pollution, while domestically enforcing the strict liability principle under Law No. 32/2009. This legal mechanism enables the state to pursue environmental accountability without proving negligence, thereby strengthening enforcement againstpolluters and securing compensation for material and immaterial losses. Overall, this study offers insight into how Indonesia can integrate international maritime conventions with national legal instruments to defend marine ecosystems and uphold state sovereignty in maritime governance.